Flexible piezoresistive sensor for vibration and sound test and preparation method and application thereof
By designing surface microstructures and inner pore structures in flexible piezoresistive sensors, and combining porous materials with composite micro pyramid array hierarchical structures, the problem of difficult to balance between high sensitivity and wide response ranges is solved, and effective response to high-frequency vibration and acoustic applications is achieved.
Patent Information
- Application Number
- CN202510023196.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
AI Technical Summary
Existing flexible piezoresistive sensors are difficult to balance between achieving high sensitivity and wide response ranges and are limited in high frequency or acoustic applications.
A flexible piezoresistive sensor consisting of a flexible substrate, soft electrode and sensing unit with low Young's modulus and high conductivity is improved by designing surface microstructures, inner pore structures and optimizing conductive materials, combining porous materials with composite micro pyramid array hierarchical structures to improve the sensor's response performance.
It significantly improves the response relaxation time and sensitivity of the flexible piezoresistive sensor, can clearly detect high-frequency responses over 20kHz, widens the application scenarios of the sensor, and achieves fast response and high mechanical stability.
Smart Images

Figure CN119826952A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sensor technology, and in particular to a flexible piezoresistive sensor for vibration and sound testing, and a preparation method and application thereof. Background Art
[0002] With the rapid development of artificial intelligence technology, flexible pressure sensors are widely used in many fields such as health monitoring, entertainment activities, and human-computer interfaces. According to different working principles, flexible pressure sensors can be divided into four types: capacitive, piezoelectric, triboelectric, and piezoresistive. Among them, flexible piezoresistive sensors can convert mechanical deformation into changes in electrical signals, and have attracted much attention due to their simple structure, easy preparation, high sensitivity, and strong stability. In recent years, researchers have carried out a lot of research on piezoresistive sensors and found that microstructure is the key to achieving the required sensing characteristics. Through the design of microstructure, a series of high performance requirements such as high sensitivity, wide response range, and fast response time of flexible sensors are met, but there is still a problem that high sensitivity and wide response range are difficult to achieve at the same time. Therefore, it is urgent to prepare flexible piezoresistive sensors with both high sensitivity and wide response range. In essence, high sensitivity means that the conductive structure of the sensor can change significantly when it is subjected to external pressure; while the wide detection range requires that the electrical signal changes can be detected when it is subjected to a small pressure, and the sensitive layer material still has a recoverable sensing structure when it is subjected to a large pressure.
[0003] The most common method for preparing flexible piezoresistive sensing layers is to compound conductive materials (metal nanowires / nanoparticles, graphene, carbon nanotubes, carbon black, MXene, conductive polymers, etc.) with flexible polymers (polydimethylsiloxane (PDMS), polyurethane, melamine, etc.) by mixing, filling or dipping and coating, and to coordinate the relationship between high sensitivity and wide response range by using the good intrinsic conductivity of conductive materials and the high elasticity of flexible polymers. The current development of smart devices requires sensors to expand into a variety of application paths, such as texture recognition, sound recognition, and pressure / vibration detection, which requires sensors to respond to static pressure and high-frequency vibrations up to several thousand hertz. However, due to the characteristics of the material, the response time of flexible sensors is mostly tens of milliseconds to hundreds of milliseconds, but this type of sensor still cannot be used to detect high-frequency vibrations of hundreds or thousands of hertz, so the application of sensors in high frequencies or acoustics still requires some exploration.
[0004] In view of this, the inventor conducted in-depth research on this demand, and thus the present case was produced. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to provide a flexible piezoresistive sensor for vibration and sound testing, and a preparation method and application thereof, which is composed of a flexible substrate, a soft electrode and a sensing unit with low Young's modulus and high conductivity (a sensing layer designed based on a filler-matrix composite active material), wherein MWCNTs are selected as conductive fillers and PDMS is selected as a flexible matrix. The structure of the sensor device is improved by designing the surface microstructure, the internal pore structure, optimizing the conductive material, and the like, thereby improving the performance of the sensor. In addition, the present invention also combines porous materials with a composite micro-pyramid array hierarchical structure to propose a flexible piezoresistive sensor for vibration and sound testing. Compared with the traditional porous structure or pyramid-shaped conductive medium layer, the flexible piezoresistive sensor significantly improves the response relaxation time, and can also be used for sound detection, developing the potential of the sensor in high-frequency vibration perception and acoustic applications.
[0006] A method for preparing a flexible piezoresistive sensor for vibration and sound testing, wherein the flexible piezoresistive sensor comprises a conductive medium layer and flexible electrodes on both sides, and comprises the following steps:
[0007] (1) mixing a polydimethylsiloxane (PDMS) precursor and a curing agent in a mass ratio of (10-15):1 and stirring to obtain a PDMS prepolymer;
[0008] (2) subjecting the PDMS prepolymer obtained in step (1) to a vacuum degassing treatment, and after completion, adding MWCNTs at a mass ratio of PDMS prepolymer to multi-walled carbon nanotubes (MWCNTs) of (10-15):1, and then adding NaCl particles at a mass ratio of PDMS prepolymer to NaCl particles of 1:(2-5), and stirring so that the NaCl particles and MWCNTs can be evenly dispersed in the PDMS prepolymer to obtain a PDMS / MWCNTs / NaCl mixed slurry;
[0009] (3) filling the PDMS / MWCNTs / NaCl mixed slurry obtained in step (2) onto a mold that has been previously etched to prepare a surface micro-pyramid groove structure, and curing it in an oven at 80 to 100° C. for 1 to 2 h to prepare a PDMS / MWCNTs / NaCl composite film with a surface pyramid structure;
[0010] (4) soaking the PDMS / MWCNTs / NaCl composite film obtained in step (3) in hot water at 60 to 80° C. for 16 to 24 hours, and then drying to obtain a PDMS / MWCNTs composite film having a porous material composite micro-pyramid hierarchical structure;
[0011] (5) performing vacuum degassing treatment on the PDMS prepolymer obtained in step (1), and after completion, adding MWCNTs to the PDMS prepolymer according to a mass ratio of PDMS prepolymer to MWCNTs of (10-15):1, and stirring the PDMS prepolymer so that the MWCNTs can be evenly dispersed in the PDMS prepolymer to obtain a PDMS / MWCNTs mixed slurry;
[0012] (6) using a scraper to prepare a PDMS / MWCNTs conductive film on a pre-treated glass plate using the PDMS / MWCNTs mixed slurry obtained in step (5);
[0013] (7) connecting the PDMS / MWCNTs composite film obtained in step (4) and the PDMS / MWCNTs conductive film obtained in step (6) via the PDMS / MWCNTs mixed slurry obtained in step (5) to prepare a conductive dielectric layer;
[0014] (8) Flexible electrodes are respectively arranged on the upper and lower surfaces of the conductive medium layer obtained in step (7), one end of the flexible electrode is connected to the conductive medium layer, and the other end extends outward and is connected through conductive silver glue and copper wire.
[0015] Preferably, the PDMS precursor in step (1) is Dow Corning Sylgard 184A main body, and the curing agent is Dow Corning Sylgard 184 B supporting curing agent.
[0016] Preferably, in the step (2), the NaCl particles and the MWCNTs are stirred by a ball mill at a rate of 250 to 350 rpm for 60 to 80 min to be uniformly dispersed in the PDMS prepolymer. By adding the NaCl particles and the MWCNTs to the PDMS prepolymer, the conductive slurry is too viscous and the magnetic stirring force is too low to achieve uniform stirring, so a ball mill is used for stirring.
[0017] Preferably, in the step (5), the MWCNTs are uniformly dispersed in the PDMS prepolymer by magnetic stirring at a rate of 750 to 850 rpm for 30 to 60 min.
[0018] Preferably, in the step (2) and the step (5), the PDMS prepolymer is subjected to a vacuum degassing treatment by evacuating the mixture to 0.09 to 0.1 kPa and maintaining the vacuum for 30 to 40 minutes.
[0019] Preferably, in step (2), the NaCl particles have a particle size of 1 to 5 μm, the MWCNTs have a length of 10 to 30 μm, an inner diameter of 5 to 10 nm, and an outer diameter of 10 to 30 nm. The NaCl particles with a particle size of 1 to 5 μm can be obtained by ball milling.
[0020] Preferably, in step (4), the PDMS / MWCNTs / NaCl composite film is dried in an oven at 50-70° C. for 1-2 hours after being soaked in hot water.
[0021] Preferably, the pretreatment of the glass plate in step (6) is ultrasonic washing in alcohol for 5 to 10 minutes.
[0022] Preferably, in step (8), the area of the flexible electrode is larger than the area of the conductive medium layer. By setting the area of the flexible electrode larger than the area of the conductive medium layer, the sensing medium layer can be fully covered, and the signal change can be transmitted more evenly.
[0023] The present invention also provides a flexible piezoresistive sensor for vibration and sound testing obtained by the above preparation method.
[0024] The present invention also provides application of the flexible piezoresistive sensor for vibration and sound testing in vibration testing.
[0025] The present invention also provides application of the flexible piezoresistive sensor for vibration and sound testing in sound testing.
[0026] The beneficial effects produced by the technical solution of the present invention are as follows:
[0027] (1) The present invention controls the porosity of the prepared PDMS / MWCNTs composite film to 40% to 80% by adjusting the ratio of NaCl particles to PDMS prepolymer, and limits the pore size of the porous structure of the composite film to the range of 1 to 20 μm, wherein the small pore size is used to improve the sensitivity of the sensor, and the large pore size can improve the compression performance of the sensor. In addition, the PDMS / MWCNTs composite film prepared by the present invention includes a multi-level pore structure and a micro-pyramid hierarchical structure with pores, has high compression performance, can effectively improve the sensitivity of the sensor, expand the linear range, and clearly detect high-frequency responses exceeding 20kHz, thereby improving the performance of the sensor, which can not only achieve accurate tracking of dynamic vibrations, but also can be used for acoustic applications, broadening the application scenarios of flexible piezoresistive sensors, and is easy to operate and highly achievable.
[0028] (2) The present invention uniformly disperses MWCNTs in the PDMS prepolymer to improve the elasticity of the porous material, so that the porous structure can quickly return to its initial state after deformation, avoiding the problem of the electrode coating being easily separated from the conductive medium layer during the strain process, thereby reducing energy loss. By designing a strong bond between the microstructure and the electrode, the sensor achieves a fast response relaxation time and high mechanical stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 This is a schematic diagram of the structure of the flexible piezoresistive sensor prepared in Example 1;
[0031] Figure 2 The surface morphology of the PDMS / MWCNTs composite film with a porous material composite micro-pyramid hierarchical structure prepared in Example 1;
[0032] Figure 3 This is a cross-sectional morphology diagram of the flexible piezoresistive sensor prepared in Example 1;
[0033] Figure 4 This is a micro stress detection diagram of the flexible piezoresistive sensor prepared in Example 1;
[0034] Figure 5 This is a sensitivity signal detection diagram of the flexible piezoresistive sensor prepared in Example 1;
[0035] Figure 6 This is a time-frequency corresponding signal diagram obtained by detecting vibration signals of different frequencies of the flexible piezoresistive sensor prepared in Example 1;
[0036] Figure 7 This is a time-frequency corresponding signal diagram obtained by testing the flexible piezoresistive sensor prepared in Example 1 under a 5000 Hz dynamic vibration signal;
[0037] Figure 8 Acoustic signal acquisition diagrams obtained by the flexible piezoresistive sensor and the acoustic sensor prepared in Example 1;
[0038] Fig. 9 The spectrum diagrams of the collected sound signals corresponding to the flexible piezoresistive sensor and the sound sensor prepared in Example 1 respectively;
[0039] Fig.10 This is a comparison chart of the sensitivity of the flexible piezoresistive sensor prepared in Example 1 at 0-30 kPa under different material ratios;
[0040] Fig.11 This is a stress-strain relationship diagram of the porous material composite micro-pyramid hierarchical structure film prepared in Example 1, the porous structure film of Comparative Example 1, and the pure pyramid structure film of Comparative Example 2. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Therefore, the following detailed description of the embodiments provided by the present invention is not intended to limit the scope of the claimed invention, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] This embodiment fully analyzes the problems in the prior art that flexible piezoresistive sensors have difficulty in achieving both high sensitivity and wide response range, and have limited applications in high frequencies or acoustics, and provides a flexible piezoresistive sensor for vibration and sound testing, a preparation method thereof, and an application thereof. The specific embodiments are as follows:
[0043] A method for preparing a flexible piezoresistive sensor for vibration and sound testing, wherein the flexible piezoresistive sensor comprises a conductive medium layer and flexible electrodes on both sides, and comprises the following steps:
[0044] (1) mixing a polydimethylsiloxane (PDMS) precursor and a curing agent in a mass ratio of (10-15):1 and stirring to obtain a PDMS prepolymer;
[0045] (2) subjecting the PDMS prepolymer obtained in step (1) to a vacuum degassing treatment, and after completion, adding MWCNTs at a mass ratio of PDMS prepolymer to multi-walled carbon nanotubes (MWCNTs) of (10-15):1, and then adding NaCl particles at a mass ratio of PDMS prepolymer to NaCl particles of 1:(2-5), and stirring so that the NaCl particles and MWCNTs can be evenly dispersed in the PDMS prepolymer to obtain a PDMS / MWCNTs / NaCl mixed slurry;
[0046] (3) filling the PDMS / MWCNTs / NaCl mixed slurry obtained in step (2) onto a mold that has been previously etched to prepare a surface micro-pyramid groove structure, and curing it in an oven at 80 to 100° C. for 1 to 2 h to prepare a PDMS / MWCNTs / NaCl composite film with a surface pyramid structure;
[0047] (4) soaking the PDMS / MWCNTs / NaCl composite film obtained in step (3) in hot water at 60 to 80° C. for 16 to 24 hours, and then drying to obtain a PDMS / MWCNTs composite film having a porous material composite micro-pyramid hierarchical structure;
[0048] (5) performing vacuum degassing treatment on the PDMS prepolymer obtained in step (1), and after completion, adding MWCNTs to the PDMS prepolymer according to a mass ratio of PDMS prepolymer to MWCNTs of (10-15):1, and stirring the PDMS prepolymer so that the MWCNTs can be evenly dispersed in the PDMS prepolymer to obtain a PDMS / MWCNTs mixed slurry;
[0049] (6) using a scraper to prepare a PDMS / MWCNTs conductive film on a pre-treated glass plate using the PDMS / MWCNTs mixed slurry obtained in step (5);
[0050] (7) connecting the PDMS / MWCNTs composite film obtained in step (4) and the PDMS / MWCNTs conductive film obtained in step (6) via the PDMS / MWCNTs mixed slurry obtained in step (5) to prepare a conductive dielectric layer;
[0051] (8) Flexible electrodes are respectively arranged on the upper and lower surfaces of the conductive medium layer obtained in step (7), one end of the flexible electrode is connected to the conductive medium layer, and the other end extends outward and is connected through conductive silver glue and copper wire.
[0052] As a preferred embodiment, the PDMS precursor in step (1) is Dow Corning Sylgard 184A main body, and the curing agent is Dow Corning Sylgard 184 B supporting curing agent.
[0053] As a preferred embodiment, in the step (2), the NaCl particles and the MWCNTs are stirred by a ball mill at a rate of 250 to 350 rpm for 60 to 80 min to be uniformly dispersed in the PDMS prepolymer. By adding the NaCl particles and the MWCNTs to the PDMS prepolymer, the conductive slurry is too viscous and the magnetic stirring force is too low to achieve uniform stirring, so a ball mill is used for stirring.
[0054] As a preferred embodiment, in the step (5), the MWCNTs are uniformly dispersed in the PDMS prepolymer by magnetic stirring at a rate of 750 to 850 rpm for 30 to 60 min.
[0055] As a preferred embodiment, the PDMS prepolymer is subjected to vacuum degassing treatment in step (2) and step (5) by evacuating the PDMS prepolymer to 0.09-0.1 kPa and maintaining the vacuum for 30-40 minutes.
[0056] As a preferred embodiment, the particle size of the NaCl particles in step (2) is 1-5 μm, the length of the MWCNTs is 10-30 μm, the inner diameter is 5-10 nm, and the outer diameter is 10-30 nm. The NaCl particles with a particle size of 1-5 μm can be obtained by ball milling.
[0057] As a preferred embodiment, the drying condition of the PDMS / MWCNTs / NaCl composite film after being soaked in hot water in step (4) is to place it in an oven at 50-70° C. and dry it for 1-2 hours.
[0058] As a preferred embodiment, the pretreatment of the glass plate in step (6) is ultrasonic washing in alcohol for 5 to 10 minutes.
[0059] As a preferred embodiment, the area of the flexible electrode in step (8) is larger than the area of the conductive medium layer. By setting the area of the flexible electrode larger than the area of the conductive medium layer, the sensing medium layer can be fully covered, and the signal change can be transmitted more evenly.
[0060] The present invention also provides a flexible piezoresistive sensor for vibration and sound testing obtained by the above preparation method.
[0061] The present invention also provides application of the flexible piezoresistive sensor for vibration and sound testing in vibration testing.
[0062] The present invention also provides application of the flexible piezoresistive sensor for vibration and sound testing in sound testing.
[0063] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. The PDMS precursor and curing agent used in the following embodiments are Dow Corning Sylgard 184 A main body produced by Dow Corning Corporation of the United States, and the curing agent is Dow Corning Sylgard 184 B matching curing agent.
[0064] Example 1
[0065] A method for preparing a flexible piezoresistive sensor for vibration and sound testing comprises the following steps:
[0066] (1) mixing a polydimethylsiloxane (PDMS) precursor and a curing agent in a mass ratio of 10:1 and uniformly stirring by magnetic stirring to obtain a PDMS prepolymer at a stirring rate of 500 rpm for 10 min;
[0067] (2) subjecting the PDMS prepolymer obtained in step (1) to a vacuum degassing treatment, and after completion, adding MWCNTs at a mass ratio of 10:1 between the PDMS prepolymer and multi-walled carbon nanotubes (MWCNTs), and then adding NaCl particles at a mass ratio of 1:4 between the PDMS prepolymer and NaCl particles, and stirring by ball milling so that the NaCl particles and MWCNTs can be evenly dispersed in the PDMS prepolymer to obtain a PDMS / MWCNTs / NaCl mixed slurry, the stirring rate being 300 rpm, and the stirring time being 60 min;
[0068] (3) filling the PDMS / MWCNTs / NaCl mixed slurry obtained in step (2) onto a mold that has been previously etched to prepare a surface micro-pyramid groove structure, and curing it in an oven at 80° C. for 2 h to prepare a PDMS / MWCNTs / NaCl composite film with a surface pyramid structure;
[0069] (4) soaking the PDMS / MWCNTs / NaCl composite film obtained in step (3) in hot water at 80° C. for 16 h, and then drying it in an oven at 60° C. for 2 h to obtain a PDMS / MWCNTs composite film having a porous material composite micro-pyramid hierarchical structure;
[0070] (5) performing vacuum degassing on the PDMS prepolymer obtained in step (1), and after completion, adding MWCNTs to the PDMS prepolymer according to a mass ratio of PDMS prepolymer to MWCNTs of 10:1, and uniformly dispersing the MWCNTs in the PDMS prepolymer by magnetic stirring to obtain a PDMS / MWCNTs mixed slurry;
[0071] (6) using a scraper to prepare a PDMS / MWCNTs conductive film on a pre-treated glass plate using the PDMS / MWCNTs mixed slurry obtained in step (5), and curing it in an oven at 80° C. for 1 h;
[0072] (7) connecting the PDMS / MWCNTs composite film obtained in step (4) and the PDMS / MWCNTs conductive film obtained in step (6) via the PDMS / MWCNTs mixed slurry obtained in step (5), and curing them in an oven at 80° C. for 1 h to prepare a conductive dielectric layer;
[0073] (8) Flexible electrodes are respectively arranged on the upper and lower surfaces of the conductive medium layer obtained in step (7), one end of the flexible electrode is connected to the conductive medium layer, and the other end extends outward and is connected through a conductive silver glue and a copper wire to obtain a Figure 1 The flexible piezoresistive sensor shown.
[0074] Example 2
[0075] The difference between Example 2 and Example 1 is that in step (2), NaCl particles are added at a mass ratio of PDMS prepolymer to NaCl particles of 1:2. The other steps are the same as those in Example 1.
[0076] Example 3
[0077] The difference between Example 3 and Example 1 is that in step (2), NaCl particles are added at a mass ratio of PDMS prepolymer to NaCl particles of 1:3. The other steps are the same as those in Example 1.
[0078] Example 4
[0079] The difference between Example 4 and Example 1 is that in step (2), NaCl particles are added at a mass ratio of PDMS prepolymer to NaCl particles of 1:5. The other steps are the same as those in Example 1.
[0080] Comparative Example 1
[0081] The difference between this comparative example 1 and the example 1 is that in step (2), NaCl particles are added at a mass ratio of PDMS prepolymer to NaCl particles of 1:1. The other steps are the same as those in the example 1.
[0082] Comparative Example 2
[0083] A method for preparing a flexible piezoresistive sensor having a porous film structure comprises the following steps:
[0084] (1) mixing a polydimethylsiloxane (PDMS) precursor and a curing agent in a mass ratio of 10:1 and uniformly stirring by magnetic stirring to obtain a PDMS prepolymer at a stirring rate of 500 rpm for 10 min;
[0085] (2) subjecting the PDMS prepolymer obtained in step (1) to a vacuum degassing treatment, and after completion, adding MWCNTs at a mass ratio of 10:1 between the PDMS prepolymer and multi-walled carbon nanotubes (MWCNTs), and then adding NaCl particles at a mass ratio of 1:4 between the PDMS prepolymer and NaCl particles, and stirring by ball milling so that the NaCl particles and MWCNTs can be evenly dispersed in the PDMS prepolymer to obtain a PDMS / MWCNTs / NaCl mixed slurry, the stirring rate being 300 rpm, and the stirring time being 60 min;
[0086] (3) coating the PDMS / MWCNTs / NaCl mixed slurry obtained in step (2) on a smooth silicon wafer, and curing it in an oven at 80° C. for 2 h to obtain a PDMS / MWCNTs / NaCl composite film;
[0087] (4) soaking the PDMS / MWCNTs / NaCl composite film obtained in step (3) in hot water at 80° C. for 16 h, and then drying it in an oven at 60° C. for 2 h to obtain a porous PDMS / MWCNTs composite film with a smooth surface, thereby obtaining a conductive dielectric layer;
[0088] (5) Flexible electrodes are respectively arranged on the upper and lower surfaces of the conductive medium layer obtained in step (4), one end of the flexible electrode is connected to the conductive medium layer, and the other end extends outward and is connected through conductive silver glue and copper wire to obtain a flexible piezoresistive sensor.
[0089] Comparative Example 3
[0090] A method for preparing a flexible piezoresistive sensor having a micro-pyramid film structure comprises the following steps:
[0091] (1) mixing a polydimethylsiloxane (PDMS) precursor and a curing agent in a mass ratio of 10:1 and uniformly stirring by magnetic stirring to obtain a PDMS prepolymer at a stirring rate of 500 rpm for 10 min;
[0092] (2) subjecting the PDMS prepolymer obtained in step (1) to a vacuum degassing treatment, and after completion, adding MWCNTs according to a mass ratio of PDMS prepolymer to multi-walled carbon nanotubes (MWCNTs) of 10:1, and stirring by ball milling so that the MWCNTs can be evenly dispersed in the PDMS prepolymer to obtain a PDMS / MWCNTs mixed slurry, the stirring rate is 300 rpm, and the stirring time is 60 min;
[0093] (3) filling the PDMS / MWCNTs mixed slurry obtained in step (2) onto a mold that has been previously etched to prepare a surface micro-pyramid groove structure, and curing it in an oven at 80° C. for 2 h to obtain a PDMS / MWCNTs / NaCl composite film with a surface pyramid structure, thereby obtaining a conductive dielectric layer;
[0094] (4) Flexible electrodes are respectively arranged on the upper and lower surfaces of the conductive medium layer obtained in step (3), one end of the flexible electrode is connected to the conductive medium layer, and the other end extends outward and is connected through conductive silver glue and copper wire to obtain a flexible piezoresistive sensor.
[0095] It should be noted that the methods for the sensitivity performance test and the mechanical performance test in the present invention refer to the following methods.
[0096] Sensitivity performance test: The flexible piezoresistive sensor samples obtained in the above-mentioned embodiments 1 to 4 and comparative example 1 are fixed in a universal tensile testing machine to ensure the consistency and reliability of the test conditions. During the test, the pressure change environment in actual work is simulated by gradually applying external stresses of different amplitudes, and the corresponding output signal value of the sensor is accurately recorded. In order to further quantify the sensor's responsiveness to pressure changes, the formula is used to calculate the relative rate of change of the output value (ΔR / R0, where ΔR is the output signal change, and R0 is the initial output signal value) to obtain the sensitivity of the sensor at each stress level. By comparing and analyzing the test results of each embodiment 1 to 4 with those of comparative example 1, the influence of material formulation or structural design on the sensitivity performance of the sensor can be intuitively understood. This testing method can not only verify the performance of flexible piezoresistive sensors under different working conditions, but also provide an important reference for subsequent optimization design. For details of relevant test data and analysis results, see Fig.10 , which shows in detail the sensitivity curves of the sensor under different stresses and the performance differences.
[0097] Mechanical properties test: The flexible piezoresistive sensors obtained in the above-mentioned Example 1, Comparative Example 2 and Comparative Example 3 are used as research objects, and the electronic tensile testing machine is used to conduct a systematic stress-strain performance test on them to evaluate their mechanical response characteristics and stability under different loading and unloading conditions. First, the sensor sample is fixed in the pressure test platform of the electronic tensile testing machine to ensure that the sensor is firm and does not slide, so as to avoid the occurrence of test errors. At the beginning of the experiment, the equipment applies strain to the sensor at a preset constant loading rate, so that the sample is gradually subjected to external force, and the corresponding stress value is recorded in real time. Subsequently, after reaching the predetermined maximum strain value, the testing machine performs strain unloading at the same rate, gradually reducing the external force to zero. The whole process constitutes a complete loading / unloading strain cycle. During the cycle, the testing equipment collects the relationship data between stress and strain in real time and draws a stress-strain curve. Under normal circumstances, the curve forms a closed hysteresis loop, which reflects the energy consumption characteristics, elastic recovery ability and plastic deformation of the sensor material under repeated stress. By comparing the test results of Example 1 with those of Comparative Examples 2 to 3, the influence of different materials or structural designs on the stress-strain performance of the sensor can be intuitively revealed. For detailed experimental results, see Fig.11 , which clearly shows the stress-strain curves of each sensor sample in multiple loading / unloading strain cycles and the characteristic differences of the closed loop. These test results provide an important reference for further optimizing the mechanical properties and application scenario adaptability of the sensor.
[0098] Figure 2The surface morphology of the porous material composite micro-pyramid hierarchical structure conductive film prepared in Example 1 is that by arranging a regularly arranged micro-pyramid array structure on the surface of the conductive film, the conductive film will produce more obvious deformation or response when subjected to external stimuli such as pressure and temperature, thereby significantly improving the sensitivity of the sensor. The introduction of the porous structure increases the strain range of the conductive film structure.
[0099] Figure 3 This is a cross-sectional morphology diagram of the flexible piezoresistive sensor prepared in Example 1. The conductive film and the pyramid composite film are integrally connected via the PDMS / MWCNTs mixed slurry, which facilitates integration and precise sensing, while also improving the stability of the sensor.
[0100] Figure 4 This is a micro stress limit detection diagram of the flexible piezoresistive sensor prepared in Example 1. The electrical signal response of the sensor to pressure is measured by dripping water droplets. The sensor shows a rapid response to the small pressure changes (≈1.25Pa) caused by the loading and unloading of water droplets. It can be seen that the core advantage of the flexible piezoresistive sensor prepared in this Example 1 is that it can produce a highly sensitive electrical signal response to small stresses. This excellent performance is significantly better than similar sensors in the prior art, making it show outstanding advantages in sensing subtle stress changes. Traditional piezoresistive sensors often have problems of slow response or high detection limit when dealing with small stresses, which limits their application in the field of precision detection. The sensor designed by the present invention significantly improves the response ability to extremely low stress by optimizing the material formulation and structural design. Specifically, the sensor can generate a stable electrical signal output at a lower stress limit, thereby realizing reliable perception of subtle pressure signals. This feature is particularly suitable for application scenarios that require strict requirements on small stress changes, such as biomedical monitoring, flexible electronic devices, and precision control.
[0101] Figure 5 This is a sensitivity signal detection diagram of the flexible piezoresistive sensor prepared in Example 1. The sensor sensitivity is 0.71 kPa -1 and 0.024 kPa -1 , corresponding to the ranges of 0~80kPa and 80~1000kPa respectively.
[0102] Figure 6 This is a time-frequency signal diagram of the flexible pressure sensor prepared in Example 1 obtained by detecting vibration signals of different frequencies. It can be seen that the flexible piezoresistive sensor prepared in the present application can stably output electrical signals regardless of whether it is at a low frequency of 200 Hz or a high frequency of 20 kHz. The corresponding frequency of the sensor at this time is calculated through Fourier transform, indicating that the sensor has a wide frequency detection range.
[0103] Figure 7 In order to carry out a vibration test on the flexible piezoresistive sensor prepared in Example 1, when the flexible piezoresistive sensor prepared in this application detects a dynamic sweep frequency signal of 0-5000 Hz, the flexible piezoresistive sensor can accurately detect the waveform of the sweep frequency signal. It can be seen that the flexible piezoresistive sensor prepared in this application has good frequency response characteristics for the entire sensing system.
[0104] Figure 8 The flexible piezoresistive sensor prepared in Example 1 and a conventional commercial sound sensor were used to collect sound respectively, and it was found that the waveforms of the two were roughly the same. Fig. 9 The sound spectrum diagram obtained by wavelet transform analysis of the flexible piezoresistive sensor prepared in Example 1 and the conventional commercial sound sensor further verified that the signals recorded by the microphone and the sensor were highly consistent in the frequency domain, indicating the potential of the flexible piezoresistive sensor prepared in this application in acoustic applications.
[0105] In order to study the effect of porosity on the sensitivity performance of the sensor, the sensitivity signal of the flexible piezoresistive sensors prepared in Examples 1 to 4 and Comparative Example 1 was tested. The results are as follows: Fig.10 As shown, when the mass ratio of PDMS prepolymer to NaCl particles is 1:4, the obtained flexible piezoresistive sensor has the best sensitivity, and the porosity is 80%. Among them, the porosity of the flexible piezoresistive sensor obtained in Comparative Example 1 is less than 40%, which cannot meet the basic porous structure; and when the mass ratio of PDMS prepolymer to NaCl particles reaches 1:5, the surface microstructure has been damaged. It can be seen that only when the mass ratio of PDMS prepolymer to NaCl particles is 1: (2 to 5), the sensitivity performance of the flexible piezoresistive sensor of the present application is better.
[0106] In order to study the effect of porous structure and micro-pyramid hierarchical structure on mechanical properties, the stress-strain relationship of the films prepared in Example 1, Comparative Example 2 and Comparative Example 3 was tested. The results are as follows: Fig.11 As shown in the figure, with the stress change, the porous structure has high plastic deformation ability but poor mechanical properties, and the surface microstructure has good elasticity but poor fatigue resistance. The porous composite pyramid microstructure has the most balanced performance and is expected to be used in subsequent flexible sensor applications.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a flexible piezoresistive sensor for vibration and sound testing, wherein the flexible piezoresistive sensor comprises a conductive medium layer and flexible electrodes on both sides, characterized in that: The following steps are involved: (1) mixing a polydimethylsiloxane (PDMS) precursor and a curing agent in a mass ratio of (10-15):1 and stirring to obtain a PDMS prepolymer; (2) subjecting the PDMS prepolymer obtained in step (1) to a vacuum degassing treatment, and after completion, adding MWCNTs at a mass ratio of PDMS prepolymer to multi-walled carbon nanotubes (MWCNTs) of (10-15):1, and then adding NaCl particles at a mass ratio of PDMS prepolymer to NaCl particles of 1:(2-5), and stirring so that the NaCl particles and MWCNTs can be evenly dispersed in the PDMS prepolymer to obtain a PDMS / MWCNTs / NaCl mixed slurry; (3) filling the PDMS / MWCNTs / NaCl mixed slurry obtained in step (2) onto a mold that has been previously etched to prepare a surface micro-pyramid groove structure, and curing it in an oven at 80 to 100° C. for 1 to 2 h to prepare a PDMS / MWCNTs / NaCl composite film with a surface pyramid structure; (4) soaking the PDMS / MWCNTs / NaCl composite film obtained in step (3) in hot water at 60 to 80° C. for 16 to 24 hours, and then drying to obtain a PDMS / MWCNTs composite film having a porous material composite micro-pyramid hierarchical structure; (5) performing vacuum degassing treatment on the PDMS prepolymer obtained in step (1), and after completion, adding MWCNTs to the PDMS prepolymer according to a mass ratio of PDMS prepolymer to MWCNTs of (10-15):1, and stirring the PDMS prepolymer so that the MWCNTs can be evenly dispersed in the PDMS prepolymer to obtain a PDMS / MWCNTs mixed slurry; (6) using a scraper to prepare a PDMS / MWCNTs conductive film on a pre-treated glass plate using the PDMS / MWCNTs mixed slurry obtained in step (5); (7) connecting the PDMS / MWCNTs composite film obtained in step (4) and the PDMS / MWCNTs conductive film obtained in step (6) via the PDMS / MWCNTs mixed slurry obtained in step (5) to prepare a conductive dielectric layer; (8) Flexible electrodes are respectively arranged on the upper and lower surfaces of the conductive medium layer obtained in step (7), one end of the flexible electrode is connected to the conductive medium layer, and the other end extends outward and is connected through conductive silver glue and copper wire.
2. The method for preparing a flexible piezoresistive sensor for vibration and sound testing according to claim 1, characterized in that: In the step (2), the NaCl particles and the MWCNTs are stirred by a ball mill at a speed of 250 to 350 revolutions per minute for 60 to 80 minutes, and are uniformly dispersed in the PDMS prepolymer.
3. The method for preparing a flexible piezoresistive sensor for vibration and sound testing according to claim 1, characterized in that: In the step (5), the MWCNTs are uniformly dispersed in the PDMS prepolymer by magnetic stirring at a rate of 750 to 850 rpm for 30 to 60 min.
4. The method for preparing a flexible piezoresistive sensor for vibration and sound testing according to claim 1, characterized in that: In the step (2) and the step (5), the PDMS prepolymer is subjected to a vacuum degassing treatment by evacuating the vacuum to 0.09-0.1 kPa and maintaining the vacuum to 30-40 minutes.
5. The method for preparing a flexible piezoresistive sensor for vibration and sound testing according to claim 1, characterized in that: The particle size of the NaCl particles in step (2) is 1-5 μm, the length of the MWCNTs is 10-30 μm, the inner diameter is 5-10 nm, and the outer diameter is 10-30 nm.
6. The method for preparing a flexible piezoresistive sensor for vibration and sound testing according to claim 1, characterized in that: In the step (4), the drying condition of the PDMS / MWCNTs / NaCl composite film after being soaked in hot water is to place it in an oven at 50-70° C. and dry it for 1-2 hours.
7. The method for preparing a flexible piezoresistive sensor for vibration and sound testing according to claim 1, characterized in that: In the step (8), the area of the flexible electrode is larger than the area of the conductive medium layer.
8. A flexible piezoresistive sensor for vibration and sound testing obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the flexible piezoresistive sensor for vibration and sound testing according to claim 8 in vibration testing.
10. Use of the flexible piezoresistive sensor for vibration and sound testing according to claim 8 in sound testing.